Effect of motivational climate on sportspersonship among competitive youth male and female football players - Miller, B. W.; Roberts, G. C.; Ommundsen, Y. (Scandinavian Journal of Medicine & Science in Sports, 2004)
The purpose of this study was to investigate the influence of perceived motivational climate and gender on sportspersonship behavior of competitive youth football players. Participants were 512 boy and 202 girl Norwegian youth football players (12-14 years old) competing in an international football tournament. A 222 (gender, mastery climate high and low, performance climate high and low) MANOVA produced no multivariate or interaction effects, but main effects for gender, performance climate, and mastery climate did emerge. Post hoc analyses of the simple main effects found that boys and girls were different in sportspersonship, but only in that boys were more sportspersonlike than girls on one of the four sportspersonship dimensions. Players perceiving a high mastery climate endorsed sportspersonship more than those players perceiving a low mastery climate, and players perceiving a high performance climate were less likely to endorse sportspersonship than players perceiving a low performance climate. Canonical correlation analysis revealed that a strong mastery climate was positively associated with commitment, respect for social conventions, and respect for rules and officials. A strong performance climate was negatively associated with respect and concern for social conventions and respect for rules and officials, while a positive association emerged for respect and concern for the opponent. The results of our study suggest that both boys and girls may well perceive the coach emphasizing similar criteria of success and failure and thereby a similar culture of sportspersonship, while in general a strong mastery climate leads to a higher sportspersonship orientation.